Approaching Pilgrimage
1 online resource (198)
Keywords: This volume seeks to explore pilgrimage studies as a distinctive sub-field of research, and to define its key methodological approaches and problems. Pilgrimage studies has long been influenced by such academic disciplines as anthropology and this volume considers the new insights that pilgrimage studies can offer to these disciplinary fields. Bringing together experienced pioneers and a younger generation of pilgrimage scholars, the chapters address the directions contemporary pilgrimage research is taking and how it is developing into the future. Covering topics like digital pilgrimage, multi-site pilgrimages, and long-term ethnography, with examples from Europe, the Middle East, and Japan, this is an important resource for all researchers engaging with pilgrimage.